Systematic Literature Review: The Evolution of Adaptive Governance and Practice in the Context of the Environmental Crisis - Herizal Herizal; Saddam Rassanjani; Afrijal Afrijal; Muhkrijal Muhkrijal; Marno Wance (Jurnal Ilmu Lingkungan, 2024)
This paper aims to clarify the understanding of the conceptual evolution of the adaptive governance framework, followed by an examination of implementation actions in the environmental setting. Since three approaches are recognized to be essential in navigating complex socio-ecological systems, namely adaptive management, adaptive co-management, and adaptive governance. This might lead to confusion and misunderstandings in adaptive concepts and practice. In this study, a systematic literature review was conducted using the Scopus database. A literature search was conducted in Mei 2023 using the keyword "Adaptive Governance" as the search term. As a result, despite sharing the same purpose and philosophy, each approach's work process has distinct features and scales. Adaptive governance emerges as a response to the need for holistic solutions to overcome uncertainty within the framework of complex socio-ecological systems. This is similar to adaptive co-management, although on a larger scale and context. While adaptive management is the conceptual foundation for other approaches.